Members Who Have Served in the U.S. Congress for 30 Years or More. (U.S. Congressional Research., 2008)
Lists Members of Congress whose service in the House, Senate, or both, has been 30 years or more, as of July 7, 2008. Identifies for each Member the respective party, State, chamber and years in each, and total length of service.